Rapid and maskless nanopatterning of aluminosilicate glass surface via friction-induced selective etching in HF solution. Issue 97 (21st October 2015) - Song, Chenfei; Yu, Bingjun; Wang, Mian; Qian, Linmao
<x xml:space="preserve">Abstract</x> A rapid and maskless nanofabrication method on glass was proposed, which consisted of scanning with a diamond tip and post-etching in HF solution. The masking effect on scan area is attributed to the formation of AlF3 during etching.